Effects of grinding-wheel cleaning system in application of minimum quantity lubrication technique - Ruzzi, Rodrigo de Souza; Andrade, Ricardo Bega de [UNESP]; Silva, Rosemar Batista da; Paiva, Raphael Lima de; Abrao, Alexandre Mendes; Aguiar, Paulo Roberto de [UNESP]; Bianchi, Eduardo Carlos [UNESP] (Elsevier B.V., 2020)
One of the peculiarities associated with the grinding process is the large amount of heat generation. Therefore, the cooling lubrication technique plays an important role and must be conducted efficient. Even though the conventional cooling lubrication technique generally outperforms all other techniques, its use is harmful to both the environment and the health of the operator. Thus, techniques that minimize the use of cutting fluids are necessary. Among the various techniques available, minimum quantity of lubrication (MQL) has been widely employed in machining scenarios. However, its use in grinding is questioned because of the poor surface finish generated and thermal damage due to the clogging of the abrasive wheel pores during grinding. To overcome these problems, in this study, an auxiliary cleaning system (CS) of the wheel was used to remove the chips and oil from the clogged wheel surface during grinding, while assessing the CS performance with the aim of making the MQL a technically viable cooling lubrication alternative. Grinding trials were performed on hardened steel under three different cutting conditions using the conventional (flood) cooling lubricant technique and the MQL technique, by applying a biodegradable cutting fluid, with and without the CS. The CS performance was evaluated with regard to the roughness, roundness errors, wheel wear, grinding power, microhardness and residual stresses. Results of both surface roughness and grinding wheel wear were also used to determine empirical equations comparing the traditional MQL technique and the MQL technique with auxiliary cleaning system (MQL + CS). The results showed that MQL assisted with the CS can improve the machined surface integrity, reducing the surface roughness, roundness error and the variation in the microhardness. Furthermore, the MQL + CS condition also presented lower grinding wheel wear.
Keywords: Auxiliary cleaning system; AISI 4340 steel cylindrical grinding; Minimum quantity of lubrication (MQL)